Hubungan Asupan Vitamin D dengan Kadar Glukosa Darah Penderita Diabetes Melitus Tipe 2 di Kota Yogyakarta - Safitri, Putu Nur; Aulia Dewi, Agil Dhiemitra; Syagata, Anindhita Syahbi (Poltekkes Kemenkes Yogyakarta, 2024)
The number of diabetes mellitus patients in Indonesia is increasing. Vitamin D has a function to trigger insulin receptor expression, which results in a decrease in blood glucose levels. The prevalence of DM sufferers in Indonesia was recorded at 10.9%, while the prevalence in Yogyakarta City was 18.6% of people diagnosed with diabetes. The aim of this study was to find out whether there is a relationship between vitamin D intake and blood glucose levels of individuals suffering from type 2 diabetes mellitus in the city of Yogyakarta. This research is quantitative research with a cross sectional design. The independent variable for the study was vitamin D intake and the dependent variable was blood glucose levels, determined using a purposive sampling technique, with a sample size of 49 people. The measuring tools in this research were a characteristic questionnaire, the SQ-FFQ form, and a food photo book. Spearman rho correlation test will be used to analyze the data. The results showed that subjects in Yogyakarta City consumed less vitamin D than needed based on the RDA (600 IU/day) and there was no relationship between vitamin D intake and blood glucose levels in type 2 DM sufferers in Yogyakarta City with a value of p=0.6777 (p> 0.05) and the value of r = -0.0609 shows a tendency for a weak relationship and has a negative relationship direction, meaning that the higher the intake of vitamin D, the lower the blood glucose level. Vitamin D is not related to blood glucose levels in type 2 DM sufferers.